Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1093/plcell/koab254
|View full text |Cite
|
Sign up to set email alerts
|

Mutual upregulation of HY5 and TZP in mediating phytochrome A signaling

Abstract: Phytochrome A (phyA) is the far-red (FR) light photoreceptor in plants that is essential for seedling de-etiolation under FR-rich environments, such as canopy shade. TANDEM ZINC-FINGER/PLUS3 (TZP) was recently identified as a key component of phyA signal transduction in Arabidopsis thaliana; however, how TZP is integrated into the phyA signaling networks remains largely obscure. Here, we demonstrate that ELONGATED HYPOCOTYL5 (HY5), a well-characterized transcription factor promoting photomorphogenesis, mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 117 publications
0
13
0
Order By: Relevance
“…HY5 mediates FRL induction of TANDEM ZINC-FINGER/PLUS3 (TZP) expression by directly binding to a G-box motif in the TZP promoter. Furthermore, TZP physically interacts with COP1, which inhibits COP1 interaction with HY5, ensuring its feedback regulation [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…HY5 mediates FRL induction of TANDEM ZINC-FINGER/PLUS3 (TZP) expression by directly binding to a G-box motif in the TZP promoter. Furthermore, TZP physically interacts with COP1, which inhibits COP1 interaction with HY5, ensuring its feedback regulation [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the initial identification of TZP by QTL mapping ( Loudet et al, 2008 ), several studies have reported a function for TZP in blue light and far-red light-mediated photomorphogenesis and photoperiod regulation of flowering ( Kaiserli et al, 2015 ; Perrella et al, 2018 ; Zhang et al, 2018 ; Li et al, 2021 ). The direct interaction between TZP and phyB in response to red light, as well as its association with clock and thermoregulatory components such as ELF3 ( Kaiserli et al, 2015 ) and PCH1 ( Huang et al, 2016b ), indicates that TZP integrates multiple light, temperature, and photoperiod pathways.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in response to far-red light, TZP acts as a positive regulator in phyA signaling by directly associating with and controlling phyA abundance and phosphorylation ( Zhang et al, 2018 ). In addition, a recent study revealed a mutual upregulation of TZP and ELONGATED HYPOCOTYL5 (HY5), a key positive regulator of photomorphogenesis, in transducing far-red light signaling ( Li et al, 2022 ). However, it is still unclear how TZP is involved in regulating red light signaling and whether it affects the function, stability, or nuclear localization of phyB and other red light signaling components.…”
Section: Introductionmentioning
confidence: 99%
“…HY5 directly binds to the G-box cis -element present in TANDEM ZINC-FINGER/PLUS3 ( TZP ) promoter to activate its expression in the far-red light. In turn, TZP competes with COP1 for binding of HY5, thus leading to the accumulation of HY5 that promotes phyA signaling ( Li C. et al, 2021 ). Blue light-activated CRY1 competes with AGB1 for binding of HY5, thus leading to the enhanced biochemical activity of HY5 in promoting photomorphogenesis ( Lian et al, 2018 ).…”
Section: Hy5 Is a Central Regulator Of Light Signalingmentioning
confidence: 99%